Digital Micro-entrepreneurship in Peer-to-Peer Accommodation Sector: Evidence from Sri Lanka - Lasika Madhawa Munasinghe; Terans Gunawardhana; Nishani Champika Wickramaarachchi; Ranthilaka Gedara Ariyawansa (Journal of Management and Entrepreneurship Research, 2021)
Objective: Digital micro-entrepreneurship in the tourism and hospitality industry is a novel phenomenon driven by accommodation sharing platforms like Airbnb. The purpose of the study is to explore the attributes, motivations, perceptions, benefits, and challenges faced by entrepreneurs in the peer-to-peer accommodation sector driven by the Airbnb Platform. Research Design & Methods: This study used a qualitative research design that followed inductive content analysis assisted by thematic analysis of semi-structured interviews with twelve micro-entrepreneurs who provide peer-to-peer accommodations in Sri Lanka. Findings: Peer-to-Peer accommodation entrepreneurs were motivated mainly by the curiosity to try Airbnb, followed by monetary and social gains. Amidst several challenges, such as the uncleanliness of some guests and violation of house rules, peer-to-peer micro-entrepreneurs enjoy their role as hosts and are satisfied with the overall hosting experience. Implications & Recommendations: The study provided peer-to-peer accommodation hosts a sense of empowerment and an opportunity to make their voice heard, which is crucial in developing an impartial public debate to develop the right policies for the peer-to-peer accommodation sector in Sri Lanka. Contribution & Value Added: The study contributes to the existing body of knowledge on entrepreneurship in the informal sector by viewing Airbnb hosts as informal microentrepreneurs with distinct attributes, motives, perceptions, benefits and challenges while providing valuable insights for various stakeholders in the industry.